Pelatihan Digital Marketing: Upaya Peningkatan Literasi Digital Dan Kemampuan Siswa Dalam Memanfaatkan Shopee Affiliate - Iwan Sopwandin; Yossi Rosmanah; R. Nita Restiyanah; Tri Nurmalasari; Mukti Awaludin; Sri Mulyani; Ayu Dewi Ismawati (CV. Biha Cendekia, 2025)
The development of digital technology has opened up new opportunities in the world of marketing, one of which is through the Shopee Affiliate program, which allows individuals to earn income without having their own products. This program is highly relevant for madrasah students who are already familiar with social media but lack adequate understanding and skills in digital marketing. This community service activity aims to improve digital literacy and the ability of MA Al-Hidayah Wangunsari students to utilize Shopee Affiliate productively. The activity is implemented through three stages: preparation, implementation, and evaluation. The training is delivered using interactive lectures, supported by PowerPoint and video visualizations, and includes hands-on practice simulation sessions. The results of the activity show an increase in students' understanding of how to use social media to promote affiliate products, as well as a growing interest in digital entrepreneurship among participants. This activity is expected to become an applicable non-formal learning model and can shape madrasah students who are adaptive, creative, and economically independent in facing the challenges of the digital era.